2021
DOI: 10.1001/jamanetworkopen.2021.31012
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Use of Benzodiazepines, Z-Hypnotics, and Serotonergic Drugs Among US Women and Men Before and During the COVID-19 Pandemic

Abstract: IMPORTANCEThe ongoing COVID-19 pandemic and associated mitigation measures have disrupted access to psychiatric medications, particularly for women. OBJECTIVE To assess the sex differences in trends in the prescribing of benzodiazepines, Z-hypnotics and serotonergic (selective serotonin reuptake inhibitors [SSRIs] and serotonin and norepinephrine reuptake inhibitors [SNRIs]), which are commonly prescribed for anxiety, insomnia, and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 26 publications
4
32
0
2
Order By: Relevance
“…Second, the observed prevalence of antidepressant use in our cohort (2%) was similar to pre-pandemic estimates, despite the high prevalence of depressive symptoms in this cohort during the study period [10,25]. This finding is in contrast with recent studies in non-perinatal samples showing increased exposure to antidepressants and psychotropics during the pandemic [22][23][24]. The low rate of antidepressant and psychotropic use in our cohort compared to the high prevalence of mental distress might have been caused by limited or delayed diagnosis of depression or anxiety by HCPs.…”
Section: Main Findingssupporting
confidence: 64%
See 1 more Smart Citation
“…Second, the observed prevalence of antidepressant use in our cohort (2%) was similar to pre-pandemic estimates, despite the high prevalence of depressive symptoms in this cohort during the study period [10,25]. This finding is in contrast with recent studies in non-perinatal samples showing increased exposure to antidepressants and psychotropics during the pandemic [22][23][24]. The low rate of antidepressant and psychotropic use in our cohort compared to the high prevalence of mental distress might have been caused by limited or delayed diagnosis of depression or anxiety by HCPs.…”
Section: Main Findingssupporting
confidence: 64%
“…Examples of this include the publication of premature assumptions on the beneficial or detrimental effects of medications on COVID-19 outcomes (e.g., hydroxychloroquine, non-steroidal anti-inflammatory drugs) [17,18]. Other publications have shown that some medications have been used or dispensed to a lesser extent within the general public (i.e., antibiotics, insulin) [19][20][21], whereas other medications have been prescribed or dispensed more often (i.e., psychotropics and antidepressants) [22][23][24]. However, the extent to which this phenomenon is applicable to pregnant and breastfeeding women remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies already investigated the impact of lockdown on antidepressant drug (AD) use. In particular, some studies reported an increased use of these medications during the first wave [15,16] that in some case persist also during the subsequent period of 2020 [17][18][19][20]. On the contrary, other studies found an initial reduction of AD use during the peak of the first wave followed by an increased use in the subsequent periods [21].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the need for safe and effective detoxification protocols from sedative-hypnotic medications has increased as the availability both via prescription and illicit markets has increased dramatically in recent years [ 3 ]. The COVID-19 pandemic only compounded this as rates of BZD prescriptions increased during this period and continue to remain elevated [ 4 ]. For the above reasons, discontinuing sedative-hypnotic medications should be considered after prolonged use, especially if used improperly or abused [ 5 ].…”
Section: Introductionmentioning
confidence: 99%